Efeito da suplementação com ácidos graxos ômega 3 (ω-3) nas propriedades das células estromais mesenquimais da medula óssea - Oliveira, Andreia Silva de [UNIFESP] (2018)
Mesenchymal stromal cells (MSCs) are characterized by the ability to differentiate into mesoderm cells, multiplication to maintain their undifferentiated state and expression of surface markers such as CD90 and CD73, but not CD45, in addition to others. They have ability to target the injured site and present antiinflammatories, antioxidants and immunosuppressants effects. Donor characteristics may influence the characteristics and / or effects of MSCs. This study aimed to perform dietary supplementation with omega3 polyunsaturated fatty acids in the characteristics of mesenchymal stromal cells. Wistar rats were supplemented for 28 days with eicosatetraenoic acid (EPA) and docosahexaenoic acid (DHA) (2mg/kg body weight), as MSCs were harvested, cultured and analyzed in the 4th passage (MSCs3) and compared with animal cells not supplemented (MSCs). The capacity of selfrenewal, adipogenic and osteogenic differentiation, response to hypoxia and repairing effect in a unilateral ureteral obstruction (UUO) model were analyzed. Differences in morphology and in the differentiation capacity between MSCs and MSCs3 was not observed. The latter has small capacity for selfrenewal, but both showed the same apoptotic rates under hypoxic conditions. In severe chronic diseases induced by UUO, we observed that as MSCs3 aggravated an infiltration of immune cells in relation to obstructed kidneys. In the transplanted kidneys with MSCs3, there was greater expression of superoxide dismutase1, IL10, and less IL6 production. There was no significant fibrosis in the obstructed kidneys, but there were increased levels of TGFβ1 in the UUO group. It decreased in those transplanted with MSCs3, suggesting a longterm antifibrotic effect as observed in MSCs. Our results suggest that supplementation of omega3 donors may interfere with the characteristics and effects of MSCs and supplementation should be taken into account when using these cells for therapy.